Transformaçoes ocorridas na vida de atingidos pela barragem de Irapé: O caso do Quilombo de Porto Corís - Freitas, Gilmar Fialho de (2016)
This article aims to point out the changes occured in the life story of the resettled Irapé Hydroelectric Power Plant in Jequitinhonha Vale, Minas Gerais. The study was conducted in the Community Reminiscent of Porto Coris Quilombo in Leme do Prado - MG. For this, we used as the main method the case-study, with information collected from written documents, interviews, participant observation and participation in meetings of neighborhood associations that form the resettlement. Through this study, confirmed that the life trajectory of these resettled populations at Irapé is marked by the inevitability that a forced resettlement process has. Vale do Jequitinhonha. trajectory, resettlement.